AgriTech4Kenya demo day | Highlight video - CGIAR Accelerate For Impact Platform (2025)
In June 2025, AgriTech4Kenya Demo Day concluded with a vibrant Demo Day Nairobi, where the 16 selected agri-tech startups showcased their innovative solutions to address Kenya’s most pressing food systems priorities, following the successful completion of a six-month acceleration program. Watch the Highlight Video.